Persistent epileptic spikes after recurrent posterior reversible encephalopathy syndrome in a patient with lupus nephritis: case report and literature review - Yu Chen; Yu-Cheng Chu; Shih-Chi Chen; Ting-Hui Chang; Chien-Sheng Wu (Egyptian Rheumatology and Rehabilitation)
Abstract Background Posterior reversible encephalopathy syndrome (PRES) is characterized by white matter lesions distributed mainly at the posterior brain, which may present with headache, visual disturbances, seizures, and disturbed consciousness in patients with systemic lupus erythematosus (SLE). Recurrent PRES is uncommon, but persistent seizures after PRES are even rarer. Case presentation Herein, we reported a 33-year-old Taiwanese female patient with SLE requiring long-term antiepileptics after two episodes of PRES within 5 months. The possible trigger factors were end-stage renal disease, hypertension, and immunosuppressant use. The brain magnetic resonance imaging showed hyperintense lesions in the bilateral parietal lobes, occipital lobes, and cerebellum, which was compatible with PRES. There are still unresolved clinical problems regarding the management of PRES in SLE. To investigate possible risk factors of recurrent attacks and persisted epileptic spikes, we also reviewed previous literature for recurrent PRES and antiepileptic use to provide insight into the clinical care of these patients. In our review, most patients have recent end-stage renal disease or immunosuppressant use, and the main trigger factor is severe hypertension which breaks down the blood–brain barrier, impairs cerebrovascular autoregulation, and results in the development of brain edema and therefore PRES. Conclusion Recurrent PRES may increase the risk of epilepsy. Long-term antiepileptic agents might be prescribed based on electroencephalogram findings.